Loss of acinar cell VMP1 triggers spontaneous pancreatitis in mice. Issue 7 (3rd July 2022) - Wang, Shaogui; Chao, Xiaojuan; Jiang, Xiaoxiao; Wang, Tiantian; Rodriguez, Yssa; Yang, Ling; Pacher, Pal; Ni, Hong-Min; Ding, Wen-Xing
ABSTRACT: The pathogenesis of pancreatitis has been linked to disruption of organelle homeostasis including macroautophagy/autophagy dysfunction and endoplasmic reticulum (ER) stress. However, the direct impact of aberrant organelle function on pancreatitis initiation and progression is largely unknown. Recently an ER membrane protein, VMP1 (vacuole membrane protein 1), has been reported to play a crucial role in autophagosome formation. Notably, we found that VMP1 is downregulated in both human chronic pancreatitis (CP) and experimental mouse acute pancreatitis (AP). Pancreatic acinar cell-specific vmp1 deletion promotes inflammation, acinar-to-ductal metaplasia, and fibrosis in mice, sharing histological similarities with human CP. Mechanistically, loss of pancreatic VMP1 leads to defective autophagic degradation and ER stress as well as activation of the NFE2L2/Nrf2 pathway. Genetic ablation of NFE2L2 attenuated pancreatitis in VMP1-deficient mice. Our data highlight the importance of VMP1 in modulating an integrated organelle stress response and its functional role in maintaining pancreas homeostasis in the context of CP. Abbreviations: AMY: amylase; ADM: acinar-to-ductal metaplasia; AP: acute pancreatitis; CASP3: caspase 3; CP: chronic pancreatitis; DDIT3/CHOP: DNA damage inducible transcript 3; DKO, double knockout; ER: endoplasmic reticulum; GCLC: glutamate-cysteine ligase catalytic subunit; GCLM: glutamate-cysteine ligase modifier subunit; HSPA5/BIP: heat shock protein family A (Hsp70) member 5; KO: knockout; KRT19/CK19: keratin 19; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MPO: myeloperoxidase; NFE2L2/NRF2: nuclear factor, erythroid 2 like 2; ND: normal donor; NQO1: NAD(P)H quinone dehydrogenase 1; PCNA: proliferating cell nuclear antigen; RIPA: radio-immunoprecipitation; SQSTM1/p62: sequestosome 1; SOX9: SRY-box transcription factor 9; TAP: trypsinogen activation peptide; TFEB: transcription factor EB; TUNEL: terminal deoxynucleotidyl transferase dUTP nick end labeling; UB: ubiquitin; VMP1: vacuole membrane protein 1; XBP1: X-box binding protein 1; YAP1, Yes1 associated transcriptional regulator; ZG: zymogen granule.